2015
DOI: 10.1155/2015/879712
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tai Chi in Centrally Obese Adults with Depression Symptoms

Abstract: This study examined the effects of Tai Chi, a low-impact mind-body movement therapy, on severity of depression, anxiety, and stress symptoms in centrally obese people with elevated depression symptoms. In total, 213 participants were randomized to a 24-week Tai Chi intervention program or a wait-list control group. Assessments were conducted at baseline and 12 and 24 weeks. Outcomes were severity of depression, anxiety, and stress symptoms, leg strength, central obesity, and other measures of metabolic symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 29 publications
(36 reference statements)
3
60
0
Order By: Relevance
“…Many different types of Tai Chi exist, but most consist of movement, meditation and breathing, while concentrating on the mind and maintaining low intensity [19, 20], and further modulate various aspects of the body including the physical, the psychological, mood and spirit [21]. In the theory of Chinese medicine (CM), Tai Chi can maintain the harmony between qi and the blood , keep yin and yang in balance and also enhance immunity [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Many different types of Tai Chi exist, but most consist of movement, meditation and breathing, while concentrating on the mind and maintaining low intensity [19, 20], and further modulate various aspects of the body including the physical, the psychological, mood and spirit [21]. In the theory of Chinese medicine (CM), Tai Chi can maintain the harmony between qi and the blood , keep yin and yang in balance and also enhance immunity [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…[ 44 ] A final total of 26 publications were included in the systematic review, reporting a total of 21 trials and n = 1604 participants. [ 45 70 ] Of those, 8 trials investigated the effects of Tai Chi or qigong on hypertension, [ 46 , 48 , 49 , 54 56 , 60 , 63 , 67 ] 1 on hyperlipidaemia, [ 61 ] 7 on diabetes, [ 47 , 53 , 58 , 59 , 62 , 65 , 66 , 68 70 ] 6 on overweight and obesity, [ 45 , 47 , 50 – 52 , 57 , 61 ] and 1 on the metabolic syndrome. [ 64 ] No included trials were identified which examined the effects of Tai Chi or qigong on tobacco or alcohol use.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies which met the inclusion criteria originated in Asia, including China (including Hong Kong and Taiwan), [ 47 , 49 , 61 , 63 , 67 , 68 , 70 ] Malaysia, [ 46 , 48 ] Korea, [ 54 56 ] and Thailand; [ 64 , 69 ] Europe, including France [ 50 ] and the United Kingdom; [ 60 ] the United States; [ 45 , 47 , 51 , 52 , 59 , 62 ] and Australia. [ 53 , 57 , 58 , 65 , 66 ] Below we discuss the studies included and the results of this review separately for each risk factor population. Characteristics of the included studies can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactive elderly men  Skin blood flow  Cutaneous vascular conductance  Skin temperature  VO2 Max 54 min per section, 5.1±1.8 sections per week, 11.2±3.4 years, Yang style (Wang, et al, 2001) Cognitive Function (Wu, et al, 2014) Patients with chronic systolic heart failure  MLHFQ 60 min per section, 2 sections per week, 12 weeks (Yeh, et al, 2011) Patients with MS  Questionnaire of life satisfaction 90 min per section, 2 sections per week, 6 months (Burschka, et al, 2014) Patients with fibromyalgia  SF-36 60 min per section, 2 sections per week, 12 weeks, 10 forms of Yang style Elderly with MDD under escitalopram treatment  SF-36 120 min per section, 1 sections per week, 10 weeks (Lavretsky, et al, 2011) Patients with stable symptomatic chronic heart failure  MLHFQ 55 min per section, 2 sections per week, 16 weeks (Barrow, et al, 2007) Adults (Li, et al, 2004) Anxiety Adults with borderline hypertension  State-Trait Anxiety Inventory 50 min per section, 3 sections per week, 12 weeks, 108 forms of Yang style (Tsai, et al, 2003) Central obese adults with depression  DASS anxiety score 60-90 min per section, 3 sections per week, 12 weeks, Kaimai style (Liu, et al, 2015) Patients with stable symptomatic chronic heart failure  SCL-90-R Anxiety 55 min per section, 2 sections per week, 16 weeks (Barrow, et al, 2007) Older adults with cerebral vascular disorder  GHQ Anxiety/Insomnia 50 min per section, 1 sections per week, 12 weeks, Yang style Depression Patients with MS  CES-D 90 min per section, 2 sections per week, 6 months (Burschka, et al, 2014) Patients with fibromyalgia  CES-D 60 min per section, 2 sections per week, 12 weeks, 10 forms of Yang style Female cancer survivors  Impact of Event Scale-Revised 60 min per section, 2 sections per week, 10 weeks (Reid-Arndt, et al, 2012) Central obese adults with depression  DASS depression score  CES-D 60-90 min per section, 3 sections per week, 12 weeks, Kaimai style (Liu, et al, 2015) Elderly with MDD under escitalopram treatment  Hamilton Depression Rating Score 120 min per section, 1 sections per week, 10 weeks (Lavretsky, et al, 2011) Patients with stable symptomatic chronic heart failure  SCL-90-R Depression 55 min per section, 2 sections per week, 16 weeks (Barrow, et al, 2007) Adults with functional class I or II rheumatoid arthritis  CES-D 60 min per section, 2 sections per week, 12 weeks, Yang style (Wang, 2008) Older adults with cerebral vascular disorder  GHQ severe depression 50 min per section, 1 sections per week, 12 weeks, Yang style Insomnia Patients with fibromyalgia  PSQI 60 min per section, 2 sections per week, 12 weeks, 10 forms of Yang style Patients with fibromyalgia  PSQI 90 min per section, 2 sections per week, 12 weeks, 8 forms of Yang style (Jones, et al, 2012) Older adults with cerebral vascular disorder  PSQI ...…”
mentioning
confidence: 99%